Trajetórias de formação no ensino superior: um estudo com os professores que atuam nos cursos de pedagogia da UFSM - Cavalheiro, Rejane (2006)
This research paper is linked to the Graduate Program in Education of the UFSM and is inserted into the Formation, Ways of Knowing, and Professional Development Line of Research. The thematic of the study speaks to the development of professors that perform in the Courses of Pedagogy: Young Childhood Education and Initial Years and has as its objective to investigate the trajectory of formation that these subjects build and what the repercussion of these trajectories in their conceptions of how to form future professors of Young Childhood Education and Initial Years in Elementary Education. The methodology is of the qualitative/quantitative type, occurring in two phases: one, quanti-qualitative with the intuition to trace an institutional profile of the subject; and, the other, qualitative revolving around the interpretation of interviews. The information collected in the two stages of research, having as its guide the analysis of content, was organized in Thematic Blocks and Guiding Axes, named respectively: 1) Personal Identification The influence of the family in the professor s choice of profession and the school model present in the different daily experiences of the subject; 2) Professional Position at UFSM lines that weave a professional path; 3) Performance in the Pedagogy Courses impediments to formation; 4) Basic Education Experience Circular vision of time and the certainties of formation: there is no movement from outside to inside; 5) Formation Appreciation The professors fear and its relation with the possible: the appearance of new curricular matrixes; 6) Research Appreciation Strengthening of the University and weakening of formation. The open questions of the questionnaire were divided into sub-axes following the interlacing of the quantitative and qualitative dimensions of analysis. The sub-axes are: The We in the I of each one ; Mask removing ; Bridges of demolition and The selfcontained diving gear of the teaching art ; The house of mirrors and Rollercoaster. It is from organizing in this fashion that we present the possible findings of the research.